JURIDICAL REVIEW OF MARRIAGE CONTRACTS FOR PREGNANT WOMEN: HARMONIZING ISLAMIC LAW AND INDONESIAN NATIONAL LAW ON LINEAGE AND CHILD PROTECTION - Nst, Yurizka Syahdani; Hasanah, Uswatun (Universitas Nurul Jadid, 2025)
This study discusses the legal provisions regarding marriage contracts for pregnant women from the perspective of Islamic law and national law in Indonesia, with a focus on the validity of the contract and the status and rights of children born from such marriages. The method used is library research with a normative-comparative approach through the study of the Qur’an, hadith, Compilation of Islamic Law (KHI), Law Number 1 of 1974 concerning Marriage, and Constitutional Court Decision Number 46/PUU-VIII/2010. The results of the study show that both legal systems basically allow the marriage of pregnant women in Islamic law as a form of moral responsibility and an effort to preserve offspring (hifz al-nasl), and national law through Article 53 of the KHI does not require waiting for the birth of the child, while the Constitutional Court Decision provides certainty of civil protection for children born out of wedlock based on biological evidence. This study fills a gap in the literature, which rarely conducts normative comparative analyses between Islamic law and constitutional jurisprudence regarding the implications of a child’s status. The main contribution of this research is to offer an interpretive harmonization framework that integrates biological evidence and the principle of protecting offspring to strengthen legal certainty and child protection. These findings have implications for recommendations for more coherent family law policies between religious norms and positive provisions.